Islamic perspective in Family Medicine - Mohamad, Hasbullah; Md Aris, Mohd Aznan (IIUM Press, 2022)
The Muslim physician, guided by the two primary sources of Islamic Law; the Quran and Sunnah, will possess the necessary traits of a good physician. Primary care Muslim physicians will deal with various types of patients and cases of different ages, races, religions, and social backgrounds. They need to have a good personality guided by sources of Islamic Law and upon reflecting on the life of Prophet Muhammad (PBUH). This chapter will discuss and relate most of the topics in this book on Islamic perspective and will provide simple guidelines to become a good Muslim physician.